TERMS OF ART IN FRENCH AND UZBEK LANGUAGES STUDY OF ETYMOLOGICAL CHARACTERISTICS - Gulchehra HOJIYEVA; Mekhriniso AMRULLOYEVA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is devoted to the detailed analysis of art and its role in social life, linguistic-cultural characteristics of the etymology of terms related to art in French and Uzbek languages.